Translation Techniques and Pragmatic Functions of Swear Words Found in The Movie "Don’t Look Up" - Nurfahmi*, Ardia Pramesti; Sutrisno, Adi (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2024)
The purpose of this research is to identify the use of translation techniques and pragmatic functions of swear words found in the movie “Don't Look Up”. This research is a descriptive qualitative method. The findings show that there are 117 data of cursing utterances and the most frequently used translation techniques in translating cursing utterances are reduction technique with a percentage of (37.6%) of the total data, adaptation translation technique (35%), and literal translation and transposition techniques with 9 data each (7.6%). Furthermore, discursive creation and particularization translation techniques are 2 data each (1.7%). In contrast, the least used translation techniques are modulation, amplification, and borrowing (0.8%). The second finding is that the most frequent pragmatic function of swearing utterances is expletive swearing with a percentage of 51.2%. The pragmatic function as auxiliary swearing is 21.3%, abusive swearing with a percentage of 17.9% and the least pragmatic function of swear words is humorous swearing with a percentage of 9.4%.Keywords: translation technique, pragmatic function, swear word